An unusual pharyngeal mass. (6th July 2015) - Couzins, Michael; Ishii, Hirotaka; Ward, Matthew J; Brockbank, Michael J
Abstract : A 37-year-old man presented with an abnormal pharyngeal sensation. Nasendoscopy demonstrated a mass projecting from the left pharyngeal wall, which could be pushed medially with external pressure. A CT scan demonstrated a fracture of the hyoid. On further questioning, the patient stated that he practised Jujitsu, a sport involving various strangling manoeuvres. He underwent a pharyngoscopy and out-fracturing of the hyoid, resulting in complete resolution of his symptoms. Hyoid fractures are uncommon and can be difficult to identify clinically, but the serious nature of associated complications highlights the importance of making the diagnosis.